#### Answer

22,24,26

#### Work Step by Step

Let the first even number be $x$, the second even number be $x+2$, and the first third number be $x+4$. (We can say this because even numbers are two apart from each other, so we know that if the first number is x, the following numbers will be two and four greater than x, respectively.)
Since the sum of the three numbers is $72$, we obtain:
$x+(x+2)+(x+4)=72$
$x+x+2+x+4=72$
$3x+6=72$
$3x=72-6$
$3x=66$
$x=22$
Since $x$ is 22, $(x+2)$ is 24 and $(x+4)$ is 26.